The Macronutrient Needs and Nutritional Provision for Women of Reproductive Age - Khakimovna, Karimova Mavluda (American Journal of Botany and Bioengineering, 2025)
Biomolecules, that is, proteins, fats, carbohydrates, which are considered macronutrients for the functioning of the human body, including the female organism of reproductive age, are of particular extreme importance. Macronutrients found in the composition of consumed foods belong to the category of irreplaceable nutrients. They are an important factor in the growth and development of the human body in meioria, in substance exchange reactions, in the resistance to diseases and in the increase in resistance to harmful influences of the external environment.